Buildings of Iowa - Gebhard, David (Oxford University Press, 1993)
From the first years of European settlement down to the present moment, Iowa has symbolized the heart of America. In Buildings of Iowa we are offered a wide-ranging survey of this state's architecture from the earliest Native American influences to the present. The image of Iowa as the breadbasket and agricultural center of the nation often overlooks the unity of urban and rural that is reflected in Iowa's buildings and landscape